A review of hyperfibrinolysis in cats and dogs. (13th October 2019) - Birkbeck, R.; Humm, K.; Cortellini, S.
Abstract : The fibrinolytic system is activated concurrently with coagulation; it regulates haemostasis and prevents thrombosis by restricting clot formation to the area of vascular injury and dismantling the clot as healing occurs. Dysregulation of the fibrinolytic system, which results in hyperfibrinolysis, may manifest as clinically important haemorrhage. Hyperfibrinolysis occurs in cats and dogs secondary to a variety of congenital and acquired disorders. Acquired disorders associated with hyperfibrinolysis, such as trauma, cavitary effusions, liver disease and Angiostrongylus vasorum infection, are commonly encountered in primary care practice. In addition, delayed haemorrhage reported in greyhounds following trauma and routine surgical procedures has been attributed to a hyperfibrinolytic disorder, although this has yet to be characterised. The diagnosis of hyperfibrinolysis is challenging and, until recently, has relied on techniques that are not readily available outside referral hospitals. With the recent development of point‐of‐care viscoelastic techniques, assessment of fibrinolysis is now possible in referral practice. This will provide the opportunity to target haemorrhage due to hyperfibrinolysis with antifibrinolytic drugs and thereby reduce associated morbidity and mortality. The fibrinolytic system and the conditions associated with increased fibrinolytic activity in cats and dogs are the focus of this review article. In addition, laboratory and point‐of‐care techniques for assessing hyperfibrinolysis and antifibrinolytic treatment for patients with haemorrhage are reviewed.